SISTEM CERDAS UNTUK PENENTUAN GAYA BELAJAR SISWA DALAM IMPLEMENTASI KURIKULUM MERDEKA - Novriyenni, Novriyenni; Gultom, Imeldawati; Julianti, Adelia; Wicaksana, Bintang (Jurnal Manajamen Informatika Jayakarta, 2025)
The independent curriculum requires teachers to carry out an initial assessment to determine the appropriate form of learning according to students' learning styles. This is the basis for determining appropriate learning methods for teachers to apply to each student. It is difficult to detect student learning styles at the beginning of learning. Identifying student learning styles is an important indicator of successful learning in the independent curriculum. The application of the CF method is appropriate to the problem of determining student learning styles because the criteria values ​​used in determining learning styles are mostly certain and uncertain. The results of this research are to provide recommendations to teachers whether the stimulation given to students based on learning styles is appropriate and to monitor students' cognitive development, it will be easier for teachers to organize learning according to students' learning needs by paying attention to students' learning styles. The system will produce a report sheet on the diagnosis of the percentage of children's learning styles in what areas and the stimulation that teachers can provide based on the type of learning style.